DESIGN OF A STEEL FRAME BRIDGE ON THE RONGKONG RIVER, KALIMBU VILLAGE, SABBANG DISTRICT, NORTH LUWU WITH A FOCUS ON FLOOD DISASTER MITIGATION - Kastono (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This study discusses the design of a steel truss bridge on the Rongkong River, focusing primarily on flood mitigation and structural safety. Geotechnical analysis was conducted based on Standard Penetration Test (SPT) data from two drilling points, supported by laboratory testing to determine shear strength parameters, soil classification, and groundwater level conditions. The results indicate that the soil at the site is dominated by very dense gravelly sand with an NSPT value of more than 60 at a depth of approximately two meters, making it suitable for use as a support layer for well foundations or short bored piles. The hydrological characteristics of the Rongkong River, including seasonal water level fluctuations and potential for local scour, were analyzed to ensure the long-term stability of the bridge structure. The proposed design integrates structural aspects with flood mitigation strategies through raising the girder elevation, optimizing foundation depth, and protecting against riverbed erosion. This study contributes to the development of a safe and flood-resilient bridge design based on the geotechnical and hydraulic conditions of the site.